Development of radioimmunoconjugate for diagnosis and management of head-and-neck subclinical cancer and colorectal carcinoma - Raquel Benedetto; Adriana Vidal Fernandes Massicano; Jefferson Jesus Silva; Cristian Antonio Wieczorek Villas Boas; Jair Mengatti; Elaine Bortoleti de Araújo (Universidade de São Paulo, 2018)
ABSTRACT Scientific innovations in diagnostic methods are important drivers of cancer control and prevention. Noninvasive imaging of the epidermal growth factor receptor (EGFR) in head-and-neck squamous, cell carcinoma and colorectal cancer could be valuable to select patients for EGFR-targeted therapy, as well as to monitor the efficacy and occurrence of resistance to immunotherapy. In order to develop the first Brazilian radioimmunoconjugate for diagnosis, Cetuximab has been conjugated to p-SCN-Bn-DTPA chelator and radiolabeled with Indium-111. The conjugation methodology was optimized using different mAb:DTPA molar ratios, time was then reduced for immunoconjugate preparation, besides the protein recovery' percentage increased after purification (m = 83.8 ± 0.91 %). The stability of Cetuximab-DTPA at - 20 oC was evaluated for six months, and its integrity was greater than 90% (m =93.9 ± 1.5%, N = 24). The radioimmunoconjugate with specific activity of 185 MBq/mg showed radiochemical purity above 95% (m=96.8 ± 1.31 %, N = 15). We conclude that the radioimmunoconjugate 111In-DTPA-cetuximab is stable and may be applied to the diagnosis of EGFR-positive tumors.